Problems of the Development of the Production and Creative Potential of Youth - Abidovna, Rasuleva Mavlyuda; Dadabek, Nomozov (European Journal of Life Safety and Stability (2660-9630), 2021)
As a result of strengthening the regulatory framework of the state youth policy in recent years, more than 50 legislative acts have been adopted and new structures have been created to work with youth problems to solve youth problems. information technology five important initiatives, production and creativity are inextricably linked to the potential of the employee.